Paving the Way for a Transformational Future : Lessons from Jawaharlal Nehru National Solar Mission Phase I - World Bank (Washington, DC, 2014)
Renewable energy, especially solar power, has been garnering a lot of interest from governments, international development organizations, civil society, and the private sector for the last few years. There has been a huge surge in the popularity of this important energy source from various stakeholders in India as well. On the other hand, solar power presents a formidable option for addressing pertinent issues being faced in international geopolitical and national macroeconomic arenas for the Government of India (GoI). Though the World Bank, India considers all market segments of solar power to be important; this report specifically looks at the utility-scale grid-connected segment of solar power in India. As one of the eight missions under India's National Action Plan for Climate Change (NAPCC), the Jawaharlal Nehru National Solar Mission (JNNSM) was launched in January 2010 with the aim of accelerating India's march toward grid parity in solar power. JNNSM envisages the achievement of grid parity through long-term and predictable policy, large-scale deployment, aggressive research and development (R and D), and domestic production of critical materials, components, and products along the value chain. Phase one (2010-13) of JNNSM, still under implementation, experienced enthusiastic participation from Indian and international investors in the grid-connected segment with substantial discounts to the benchmark tariffs determined by the Central Electricity Regulatory Commission (CERC) for 500 megawatt (MW) each of solar thermal and solar photovoltaic (PV) projects. Another unique feature of JNNSM phase one has been the adoption of a reverse auction method for awarding projects to qualified bidders. The GoI took several proactive steps in phase one of the mission, such as offering a bundling of solar power with unallocated coal-based power through the National Thermal Power Corporation (NTPC) Vidyut Vyapar Nigam (NVVN), implementing a renewable purchase obligation (RPO) for solar power, instituting a payment security scheme (PSS), and undertaking certain measures for promoting local manufacturing, which all combined to ensure the success of phase one.